Internalisasi Jilbab pada Wanita Muslim: Studi Fenomenologi di Kota Metro Lampung - Mat Jalil; Anton Widodo (NALAR, 2020)
This study discusses the phenomenon of veiled women in Metro Lampung City. Furthermore, the method used in this research is descriptive qualitative using the phenomenological method. The results of this study are the first is the understanding that veiled women in the metro city of religious knowledge already understand the obligation to wear good clothes, religion, or because of fear of the sins committed. the second is wearing a veil that is forced, for example in an institution enforcing special rules in wearing a veil. Due to feeling uneasy, because of the place he worked on average wearing a hijab. third, to look for comfort in life, because a woman who wears a hijab will feel protected. fourth, follow the current lifestyle. Lots of women wear hijab for work needs as a model or endorsement. And the other thing is to make it look more beautiful and modern style. The fifth is a strategy in the world of politics, namely using the veil as a tool to attract public sympathy. In a survey conducted by researchers proved that there are still many students in one of the Islamic tertiary institutions in the city of metro and the community said that he was wearing a hijab to meet the desired lifestyle or something that is a trend. Based on the survey, one of the causes underlying the use of the headscarf by students themselves can be obtained. These conditions prove that the veil is not merely due to religious knowledge. Women who wear the hijab because of a psychic background may need the peace of mind that is obtained from the hijab as Muslim women's clothing is closed to cover the whole body and is the best.Keywords: Internalisation, Hijab, Muslim Woman